Knockout IL4I1 affects macrophages to improve poor efficacy of CD19 CAR-T combined with PD-1 inhibitor in relapsed/refractory diffuse large B-cell lymphoma - Rui Zhang; Yi Zhang; Hairong Xiao; Qingxi Liu; Mingfeng Zhao (Journal of Translational Medicine)
Abstract Chimeric antigen receptor (CAR) T-cell therapy plays a critical role in the treatment of B-cell hematologic malignancies. The combination of PD-1 inhibitors and CAR-T has shown encouraging results in treating patients with relapsed/refractory (R/R) diffuse large B-cell lymphoma (DLBCL). However, there are still cases where treatment is ineffective. This study aimed to investigate the role of IL4I1 in the poor efficacy of CD19 CAR-T combined with PD-1 inhibitors in R/R DLBCL and to explore potential mechanisms. Transcriptomic and metabolomic correlation analyses were performed on tumor tissue from DLBCL patients. We employed an in vitro co-culture system consisting of Pfeiffer cells, CD19 CAR-T and macrophages to investigate the underlying mechanisms. It was found that IL4I1 levels were significantly increased in the tumor tissues of R/R DLBCL patients compared to responders. Correlation analysis revealed a positive association between IL4I1 and tryptophan (Trp)-kynurenic acid (Kyn) related metabolites. In the in vitro co-culture model, the presence of IL4I1 inhibited the cytotoxicity of CAR-T cells. Depletion of IL4I1 disrupted the IDO-AHR-Kyn signaling pathway, thereby enhancing the effectiveness of PD-1 inhibitors in combination with CD19 CAR-T for DLBCL treatment. CAR-T-mediated cytotoxicity was significantly inhibited when IL4I1 was present in the in vitro co-culture model. These findings suggest that IL4I1 may be a contributing factor to poor prognosis in R/R DLBCL patients. IL4I1 expression enhances immunosuppression via the IDO-AHR-Kyn pathway, inhibiting the effectiveness of PD-1 inhibitors combined with CD19 CAR-T. Therefore, suppression of IL4I1 may represent a potential target for combination therapy in DLBCL.